Counterterrorist detection techniques of explosives - Kagan, Avi; Oxley, Jimmie C. (Elsevier B.V., 2022)
Counterterrorist Detection Techniques of Explosives, Second Edition covers the most current techniques available for explosive detection. This completely revised volume describes the most updated research findings that will be used in the next generation of explosives detection technologies. New editors Drs. Avi Cagan and Jimmie Oxley have assembled in one volume a series of detection technologies written by an expert group of scientists. The book helps researchers to compare the advantages and disadvantages of all available methods in detecting explosives and, in effect, allows them to choose the correct instrumental screening technology according to the nature of the sample.